Ecological Modelling Applied to Entomology - Ferreira, Cláudia P.; Godoy, Wesley A.C (Entomology in Focus, 2014)
This book provides a synopsis of the major topics currently studied in entomology combining population theory with experimentation. The chapters address different ecological aspects important for agricultural and medical entomology, emphasising pest management and conservation. .